Redundant Regulation of Cdk1 Tyrosine Dephosphorylation in Saccharomyces cerevisiae. Issue 3 (29th December 2015) - Kennedy, Erin K; Dysart, Michael; Lianga, Noel; Williams, Elizabeth C; Pilon, Sophie; Doré, Carole; Deneault, Jean-Sebastien; Rudner, Adam D
Abstract: Cdk1 activity drives both mitotic entry and the metaphase-to-anaphase transition in all eukaryotes. The kinase Wee1 and the phosphatase Cdc25 regulate the mitotic activity of Cdk1 by the reversible phosphorylation of a conserved tyrosine residue. Mutation of cdc25 in Schizosaccharomyces pombe blocks Cdk1 dephosphorylation and causes cell cycle arrest. In contrast, deletion of MIH1, the cdc25 homolog in Saccharomyces cerevisiae, is viable. Although Cdk1 -Y19 phosphorylation is elevated during mitosis in mih1 ∆ cells, Cdk1 is dephosphorylated as cells progress into G1, suggesting that additional phosphatases regulate Cdk1 dephosphorylation. Here we show that the phosphatase Ptp1 also regulates Cdk1 dephosphorylation in vivo and can directly dephosphorylate Cdk1 in vitro . Using a novel in vivo phosphatase assay, we also show that PP2A bound to Rts1, the budding yeast B56-regulatory subunit, regulates dephosphorylation of Cdk1 independently of a function regulating Swe1, Mih1, or Ptp1, suggesting that PP2A Rts1 either directly dephosphorylates Cdk1 -Y19 or regulates an unidentified phosphatase.